An optimisation model for transportation of hazardous wastes. (7th April 2010) - Uddameri, Venkatesh; Honnungar, Vivekanand
The North American Free Trade Agreement (NAFTA) has considerably increased the transport of materials along the US-Mexico borders. Maquiladoras are business entities that are structured to take relative advantages offered by both countries to develop cost-effective products. Current Mexican regulations require that hazardous wastes generated by US companies be shipped back for proper disposal. The movement of hazardous wastes across the US-Mexico border is likely to increase in years to come. The broad goal of this study is to develop a decision support system to determine best routes for transporting hazardous wastes across the South Texas ndash; Mexico border and evaluate critical factors that influence the shipment of wastes. The results of the study indicate that the hazardous landfills in Texas are of significant economic value and help foster cross-border manufacturing practices. The installation of hazardous waste incinerators in South Texas could be economically beneficial for treating hazardous wastes generated in Maquiladoras close to South Texas. However, a variety of meteorological, environmental, economic and social factors must be considered to evaluate the feasibility of siting these incinerators. Conservation practices and innovative processes to minimise and possibly eliminate hazardous waste generation are however necessary for long-term sustainability of Maquiladora operations.